Perlindungan Konsumen Terhadap Sistem Pengembalian Uang Pada Pelanggan di Industri Retail - Meriza Elpha Darnia; Alfani Tiara Azmy; Arifa Fasya; Enjelinda Amelia; Fadhli Maulana; Uli Widiriyani (Universitas Sains dan Teknologi Komputer, 2023)
This research aims to understand how the legal regulations regulate consumer protection in the refund system in the retail industry, as well as to find out and understand the legal impact of the customer refund system in the retail industry. This research uses normative juridical methods. For example, buying and selling transactions require a legal medium of exchange, as regulated in Article 2 paragraph (2) of the Bank Indonesia Law which states that